Prevalence and factors influencing overweight/obesity and poor vision in children and adolescents before and after the COVID-19 pandemic in a city in Sichuan Province - Shian Liu; Nana Li; Nian Liu; Tianyu Fu; Yongkang Mao; Jingchang Du; Yanfeng Zhu (Frontiers in Public Health)
BackgroundOverweight/obesity and poor vision are currently common health problems for children and adolescents, and the change in overweight/obesity and poor vision in children and adolescents after the COVID-19 pandemic is unclear. The aim of this study was to investigate the changes in the prevalence of overweight/obesity and poor vision in children and adolescents before and after the COVID-19 pandemic, along with the influencing factors.MethodsA survey was conducted from 2019 to 2021, involving a cohort of 33,158 children and adolescents for the purpose of gathering their general demographic information and administering questionnaires. χ2 test was employed to compare the prevalence of overweight/obesity and poor vision across various demographic characteristics, while binary logistic regression was utilized to assess the statistical significance of correlation factors.ResultsThe prevalence of overweight/obesity was 25.43% in 2019, increasing to 31.28% in 2020 with the COVID-19 pandemic, and falling back to 24.64% in 2021. At the same time, the prevalence of poor vision was 68.02% in 2019, decreased to 61.30% in 2020, and recovered to 72.18% in 2021. Additionally, regression analysis revealed associations between overweight/obesity and factors such as gender, place of residence, frequency of fruit consumption, smoking status, moderate to high-intensity exercise and outdoor activity time. Factors associated with poor vision included gender, place of residence, eye exercise frequency, location of recess activities, turn off the lights when looking at electronic screens after dark, reading books or electronic screens while lying down, reading books or electronic screens when walking or riding in a car, outdoor activity time, and parental myopia.ConclusionThe COVID-19 pandemic has had profound implications for the physical and mental well-being of children and adolescents, resulting in noticeable fluctuations in rates of overweight/obesity and poor vision before and after the outbreak of the pandemic. Thus, in the widespread implementation of interventions such as home isolation, school closures, and extensive use of the internet, prioritizing the health of adolescents, timely policy adjustments, and specific preventive actions are vital in avoiding such occurrences.